Modelo colaborativo para desenvolvimento de tecnologia e inovação na indústria aeronautica nacional de pequeno porte - Camargo, Gerson Marcelo (2021)
Historically Brazil has been solidifying as an important generator of technologies for the aircraft production (MONTINI et. al, 2019). The Brazilian aeronautical sector has dozens of small companies, aircraft manufacturers that strive to survive with few resources in a highly technological competitive environment. There are some difficulties to bridging the technological barriers and certification process to grow in the market. Faced with this context, the present research aims to develop a model of technological collaboration between small companies of the national aeronautical sector, based on a sectorial technological diagnosis. Was adopted the field research method where the investigation case is based on the way in which the small companies of the aeronautical sector could collaborate mutually in order to develop new technologies. The procedures were planned and subsequently executed in a pilot test. The research procedures are based on the construction of a theoretical conceptual structure, formed by a historical mapping, theoretical models of collaboration mapping, and mapping of diagnosis and strategic positioning. The data from a sample of several companies segmented as active in aircraft manufacture or assembly, manufacture of aeronautical components or parts and aircraft maintenance, were collected and analyzed using the five forces proposed by Porter (1989) and SWOT analysis as the main analytical frame (FAUSTINO, 2014). The results highlight: a) the historical scenario of the development of small companies in the Brazilian aeronautical segment in the last 35 years; b) the small aircraft market in which these companies are players; c) a diagnosis of the level of technological development of the small aeronautical industry in Brazil; d) an analysis of the segment carried out through the 5 Porter Forces and the SWOT matrix; and finally the proposal of a model to technological collaboration that enables the segment of small national aeronautical industries to reach higher levels of evolution and competitiveness. Thus, although there is an expressive interest in a model that can develop this segment of the industry, several other technical and political barriers were detected that need to be transposed. This research is expected to contribute to the development and survival of organizations operating in the sector, especially small companies and startups that lack specialized understanding to structure work and enable operations with lower efforts and costs. Also, a model of technological collaboration that allows companies to reach higher levels of competitiveness considering the government contribution only as sector regulator and inspector. The results contemplate a system of elements whose interactions are guided by Knowledge Management that contribute to the strengthening of the national industry. The main interested in this research would be the stakeholders of aeronautical sector's that want to overcome technological and certification barriers to achieve the best positions in the general aviation market.